2013
DOI: 10.1080/13691457.2012.724388
|View full text |Cite
|
Sign up to set email alerts
|

The intersection of employment and care: evidence from a UK case study

Abstract: Working carers are a key focus of UK policies on health and social care and employment. Complementing national and European evidence, this paper presents a local case study of working carers. It draws on data from a county-wide survey containing a module on caring. Data were primarily categorical and were analysed using SPSS. Three quarters of all carers who responded to the survey were of working age: two thirds were employed and one third had been employed previously. The majority of working carers were midl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 10 publications
2
21
0
Order By: Relevance
“…; Milne et al . ). There is also evidence that employed carers in England would like more service support (Phillips et al .…”
Section: Introductionmentioning
confidence: 97%
“…; Milne et al . ). There is also evidence that employed carers in England would like more service support (Phillips et al .…”
Section: Introductionmentioning
confidence: 97%
“…, Milne et al . ). Population‐based studies of disabled or older people in the UK have also found unmet need for services (Vlachantoni et al .…”
Section: Introductionmentioning
confidence: 97%
“…Previous UK research on working carerspeople in paid employment who provide unpaid care to family or friends because of long-term physical or mental illhealth or disability, or problems related to old agehas found expressed unmet need for services (Mooney et al 2002, Phillips et al 2002, Yeandle et al 2007, Milne et al 2012. Population-based studies of disabled or older people in the UK have also found unmet need for services (Vlachantoni et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the experience of being a carer varies according to the number of hours spent caring, length of caregiving, type of care required, relationship, nature of the cared for person's needs and access to and acceptability of formal services. Older spouses tend to resist the 'intrusion' of 'outsiders' (including services) because they rarely identify themselves as 'carers'; this not only positions them in an oppositional status to their wife/husband but challenges the 'care contract' that underpins long-term marriage (Milne and Hatzidimitriadou, 2003;Arksey and Glendinning, 2007;Milne et al, 2012). Women, for example, who are the majority of carers, report higher levels of subjective burden, feel more obliged to give up paid work to care and are more reluctant to ask for an 'assessment of need' or support from services than their male counterparts (Milne and Williams, 2003).…”
Section: Carer Care and Caringmentioning
confidence: 99%